A new, diminutive species of Catopsalis (Mammalia, Multituberculata, Taeniolabidoidea) from the early Paleocene of southwestern Alberta, Canada. (20th June 2018) - Scott, Craig S.; Weil, Anne; Theodor, Jessica M.
Abstract: Multituberculates were among the most taxonomically diverse mammals of the early Paleocene, having survived the catastrophic Cretaceous-Paleogene mass extinction and radiating soon thereafter. Although their evolution during the early Paleocene saw the advent of increasingly specialized dentitions, multituberculates generally remained small, rarely exceeding body sizes greater than those of extant rabbits. A conspicuous exception is the Taeniolabidoidea, a primarily North American clade whose members include the largest multituberculates yet discovered. Taeniolabidoidea includes several genera, with one of these, Catopsalis, being speciose and geographically wide ranging. Until recently, the chronological succession of Catopsalis appeared to document a trend of increasing body size. We report here on a new species of Catopsalis from the early Paleocene of Alberta that violates this trend and suggests that the evolutionary history of Catopsalis is considerably more complex. Catopsalis kakwa new species is not only the smallest species of Catopsalis, but is the smallest taeniolabidoid so far discovered, with an estimated body mass between 400 g and 660 g. In contrast to previous studies, we used recently proposed regressions based on lower cheek tooth row length to estimate body masses for North American taeniolabidoids. Our results propose more modest body mass estimates, particularly for the largest taeniolabidoids. The occurrence of C . kakwa n. sp. in the late early Paleocene implies either a significant ghost lineage, or reversal of several characters, including body size, during the latter part of the early Paleocene; the more likely of these scenarios must await a better understanding of the phylogenetic position of C . kakwa n. sp. UUID:http://zoobank.org/66d85345-49b8-4a46-ba6e-a4d4369cb3e0 urn:lsid:zoobank.org:pub:AF7A5659-9068-4F2F-A6EC-5522A2BBA4CB